The Utilization of Physical Units to Enhance the Understanding of Fundamental Physics Concepts in Kinematics for First-Semester Biology Education Students. - Taufik, Muhammad; Sutrio (Mataram University, 2024)
The research undertakes a comprehensive examination into the efficacy of incorporating physics units to augment the comprehension of fundamental kinematic principles among first-semester students of biology education. Through meticulous investigation, a significant enhancement in student understanding is evidenced subsequent to the integration of physics-based pedagogical strategies. Analysis of pre-test and post-test data from a cohort of 29 students reveals an average pre-test score of 61.724, contrasted with an average post-test score of 90.690, indicative of a noteworthy improvement. Statistical scrutiny further unveils a mean difference of -28.966 between pre-test and post-test scores, underpinned by a 95% confidence interval ranging from -30.825 to -27.106. These findings advocate for the adoption of interdisciplinary methodologies to bolster students' grasp of basic physics concepts within the domain of biology education, underscoring the imperative of evidence-based educational practices in cultivating more efficacious learning strategies.